Estudo de neoplasias mamárias de cadelas em Uberlândia e imunomarcação para ciclooxigenase 2 - Soares, Nicolle Pereira (2015)
The cyclooxygenase 2 (Cox 2) is a molecular indicator of prognosis marker and its expression is associated with progression of mammary tumors in dogs. The purpose of this study was to investigate breast tumors of bitches Cox 2 expression by immunohistochemistry and correlated with the clinical stage, tumor size, lymph node involvement, the classification and the histological grade of carcinomas. We included in this study, 100 female dogs with mammary tumors and 131 samples were analyzed. Histological and COX 2 immunostaining evaluation were conducted. The streptavidin-biotinaperoxidase technique was used in order to do the immunohistochemistry (IHC). The IHC analysis was performaced counting the number of positive-staining cells in ten fields and the staining intensity. The COX 2 staining index was obtained by multiplying the COX 2 staining distribution and intensity scores. This gave a range of COX 2 staining indices of 0 12.Carcinoma complex was the most common histological type that we were diagnosed. The COX 2 expression was observed in the benign and malignant tumors. The weak score is more frequent, and strong score was observed in carcinomas. Simple carcinomas demonstraded a higher number of positive staining cells. There was no positive correlation between the histological type, size and lymph node involvement and the Cox 2 immunostaining. Therefore, COX 2 immunostaining is not a good prognostic factor.